2021
DOI: 10.1519/jsc.0000000000002519
|View full text |Cite
|
Sign up to set email alerts
|

Self-selected Rest Interval Improves Vertical Jump Postactivation Potentiation

Abstract: This study compared the effects of self-selected rest interval and fixed rest interval strategies on post-activation potentiation (PAP) in countermovement jump (CMJ) performance. Twelve strength-trained male's (age: 25.4 ± 3.6 years; body mass: 78.8 ± 10.5 kg; height: 175 ± 7.0 cm; half-squat 1RM: 188.7 ± 33.4 kg) performed three experimental conditions: 1) fixed rest interval (FRI: CMJ test; 4-min rest interval; 5RM back squat; 4-min rest interval; CMJ test), 2) self-selected rest interval (SSRI: CMJ test; 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Therefore, females may also show a different level of perception of fatigue from males; however, this is speculation and therefore further studies are warranted. Third, the participants in the do Carmo et al [27] study showed significantly higher levels of relative muscle strength (~2.4) than those in the Santos et al [28] study (~1.9 kg/kg body mass (b.m.) as well as ours (~1.16 kg/kg b.m.)…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Therefore, females may also show a different level of perception of fatigue from males; however, this is speculation and therefore further studies are warranted. Third, the participants in the do Carmo et al [27] study showed significantly higher levels of relative muscle strength (~2.4) than those in the Santos et al [28] study (~1.9 kg/kg body mass (b.m.) as well as ours (~1.16 kg/kg b.m.)…”
Section: Discussionmentioning
confidence: 86%
“…First, the participants in our study self-selected average intracomplex rest intervals of 262 ± 66 s for the attack jump and 197 ± 110 s for the standing spike attack (Figure 1); however, as shown by Seitz and Haff [19], intervals above 5 min are needed to enhance a greater PAPE effect than a shorter rest interval. In the case of the study by do Carmo et al [27] in which the half squat exercise improved the countermovement jump performance with self-selected intra-complex rest intervals, the participants chose a longer rest interval time of 357 ± 164 s. It can therefore be assumed that the PAPE effect was not elicited because most likely fatigue exceeded the accompanying potentiation caused by the CA applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, potentiation is the result of the balance between the mechanisms of PAPE and fatigue [6,7]. Whereas numerous studies [13][14][15]17,18] have investigated the effect of different factors that can codify this balance (e.g., volume, intensity and rest interval), the optimal work-to-rest ratios within each conditioning activity have not yet been determined in the scientific literature, especially regarding performance specific to combat sports. Due to the intermittent nature of taekwondo, alternating effort and rest times using specific ratios can be a very important factor that can affect subsequent specific performances [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although the study by Do Carmo et al [15] is a welldesigned study, it is not supported by other robust evidence. Therefore, we decided on the 1-and 3-minute intervals because the rest time was sufficient/insufficient to restore the creatine phosphate reserves [7,13].…”
Section: Discussionmentioning
confidence: 90%